The usage of a differentiated instruction strategy to teach heterogeneous english groups in a Costa Rican context - Lopez Cerdas, Cristopher (2022)
Heterogeneous groups, also called mixed ability groups or classes, are one of the most challenging student populations for English as a Foreign Language (EFL) teachers. Currently, the lack of contextual research on the realities of heterogeneous groups in Costa Rica has created a need to collect important constructive aspects that could help teachers with heterogeneous groups. This paper, summarizes key guidelines that Costa Rican teachers can follow to initially understand what heterogeneous groups are and how to address them with a differentiated instruction (DI) approach while considering the students’ needs, group work, a student-centered approach, and learning styles, to follow an informed path in teaching mixed ability students.